Finite element analysis of biomechanical effects in rat tibia during tibial cortex transverse transport - Zhen, Puxiang; Liu, Jie; Su, Hongjie; Qin, Wencong; Ding, Yi; Yang, Shenghui; Wei, Lu; Mo, Ruiqing; Nie, Xinyu; Hua, Qikai (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveDiabetic foot ulcer (DFU) poses a major clinical burden. This study, for the first time, establishes and validates a finite element (FE) biomechanical model of tibial cortex transverse transport (TTT) in diabetic rats. By integrating micro-CT data at multiple time points, we provide a novel computational approach to assess the biomechanical safety and stability of TTT, thus bridging preclinical animal research and potential clinical translation.MethodsThis study utilized a customized transverse osteotomy transport frame to establish a model of TTT for treating lower limb ischemic ulcer in diabetic rats. Postoperatively, the tibiae and fibulae Dicom were harvested by ex-vivo micro-CT scaning. The imaging data are processed and analyzed using mechanical analysis software by Mimics, 3-matic Medical, Geomagic Studio, Hypermesh, MSC.Patran, and MSC. Nastran to simulate the loading characteristics of the rat’s tibia and fibula with the TTT.Results1. Peak von Mises stresses in the transport tibial bone fragment under axial compression (7.04 Mpa), axial torsion (16.91 Mpa), and three-point bending (9.40 Mpa), showed no significant differences between postoperative time points (3, 6, 9, 12, and 30 days), indicating that the overall stress change in the tibia during the tibial transverse transport process is minimal. 2. Over 8-week healing period, dynamic load sharing occurred among the transported bone fragment, original tibia, and adjustable external fixator. Progressive healing of the transported bone fragment with the surrounding bone tissue reduced the structural bearing stress of the adjustable TTT fixation. The overall stiffness of the tibia increases as the transported fragment and tibia gradually restore, further enhancing the stability of the overall tibia. 3. Under biomechanical testing conditions including axial compression, axial torsion, and three-point bending, the application of adjustable external fixators successfully repositioned free bone fragments to their anatomical alignment in the tibia without exceeding the ultimate yield strength of cortical bone tissue. Secondary fracture initiation or catastrophic structural failure was not observed during testing. The current experimental results shows the TTT fixation satisfies the required strength criteria for rat experiment.ConclusionThe TTT rat model demonstrated biomechanical stability and surgical safety in silico, supporting its translational potential. However, further experimental validation is required.